2010
DOI: 10.1007/s11771-010-0619-9
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-modification of Ca-based bentonite via semidry process

Abstract: In order to improve the quality of Hunyuan inferior Ca-based bentonite (Ca-Bent), semidry process was used to modify Ca-Bent into superior Na-based bentonite (Na-Bent). The factors affecting sodium-modification were investigated. The optimized experimental parameters are obtained as follows: Na 2 CO 3 dosage 4.0%, ageing time 25 d, briquetting pressure 25 MPa and briquetting moisture 20%. Under the optimization conditions, the modified Na-Bent has a colloid value of 73.6 mL/(3g), dilation of 38 mL/g and water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…The green pellet strength of all the samples is over 5 times. This result is qualified and fitted with reality and other research [2,4,9,10]. Fig.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The green pellet strength of all the samples is over 5 times. This result is qualified and fitted with reality and other research [2,4,9,10]. Fig.…”
Section: Resultssupporting
confidence: 87%
“…The problem is how to decrease bentonite content and still ensure the stability and metallurgy properties of pellets. Some recent research shows the effect of modified bentonite on pellets' mechanical properties [6][7][8][9]. On the other hand, various types of binders have been investigated for use in iron ore pelletization.…”
Section: Introductionmentioning
confidence: 99%
“…The prior finding indicated that the tetrahedral and octahedral sheets have disintegrated, and the structural cations have been released, indicating that these cations have been removed from the octahedral positional structure and replaced by sodium ions. The interlamellar gap between crystals is squeezed 34 . The chemical composition and interior structure of activated Na-bentonite clay were altered.…”
Section: Resultsmentioning
confidence: 99%
“…is is an indication of the dissolution of the tetrahedral and octahedral sheets and subsequent release of the structural cations, that is, these cations have been eliminated from the octahedral positions, thereby exchanging with Na + ions. Moreover, the interlamellar spacing between crystal grains is compressed [49].…”
Section: X-ray Diffractogramsmentioning
confidence: 99%